Synthesis of zeolitic materials of IWR framework structure type from zeolitic precursor materials

By introducing Si and other tetravalent elements into the IWR framework of zeolite materials, high purity and high crystallinity zeolite materials are prepared, which solves the problem of reduced stability when germanium substances exist, and improves its performance in catalytic applications and Economical.

CN119137068APending Publication Date: 2024-12-13BASF SE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380038359.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-05
Filing Date
2023-05-04
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the prior art, zeolite materials with IWR skeleton structures are reduced in the presence of germanium substances, and germanium substances are expensive, limiting their use in heterogeneous catalyst applications, especially in epoxidation. Poor performance in the reaction.

Method used

A method is used to prepare zeolite materials with an IWR type skeleton structure, and high purity and High crystallinity zeolite material to avoid the use of germanium.

Benefits of technology

Zeolite materials that show improved physical and chemical properties in catalytic applications have achieved significantly improved catalytic effects and are cost-effective in epoxidation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005117397220000041
    Figure BDA0005117397220000041
  • Figure BDA0005117397220000101
    Figure BDA0005117397220000101
  • Figure FDA0005117397210000021
    Figure FDA0005117397210000021
Patent Text Reader

Abstract

The present invention relates to a method for preparing a zeolitic material having an IWR framework structure, as well as a zeolitic material having an IWR framework structure obtained and / or obtainable by said method, and to the use of said zeolitic material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a zeolite material having an IWR framework structure, and a zeolite material having an IWR framework structure obtained and / or obtainable by the method, and to uses of the zeolite material. Background Art

[0002] ITQ-24 zeolites with an IWR structure were first synthesized in the presence of germanium species using hexamethylammonium as an organic template. Thus, EP 1 609 758 B1 discloses zeolite Ge-ITQ-24, which is obtained by using Ge as a tetravalent element in addition to Si in its zeolite framework.

[0003] Due to its unique three-dimensional 12×10×10 ring pore structure (pore sizes of 5.8×6.8, 4.6×5.3 and ), ITQ-24 has attracted a lot of attention. However, when a large amount of germanium species is present in the IWR framework, its thermal stability and hydrothermal stability are significantly reduced. In addition, the use of germanium species in the synthesis is expensive, which strongly hinders the application of IWR zeolite as a heterogeneous catalyst. To solve this problem, Cantin, A. et al. described a Ge-free route for synthesizing IWR zeolite by introducing boron species instead of germanium in J.Am.Chem.Soc.2006, 128, pp. 4216-4217, which is due to the Si-0-Ge angle being very close to the Si-0-B angle, where pure silica IWR can also be synthesized with the assistance of seed crystals. However, from the perspective of industrial application, aluminosilicate IWR zeolite is more attractive due to its strong acidity and excellent thermal and hydrothermal stability. Due to the lack of direct synthesis of aluminosilicate IWR zeolites, Shamzhy, M. et al. in Catal. Today 2015, 243, 76-84 describe a post-synthesis treatment for aluminization of borogermanosilicate IWR zeolites.

[0004] On the other hand, WO 2020 / 244630 A discloses the direct synthesis of aluminosilicates having an IWR framework structure, wherein the obtained material does not contain germanium. As can be seen from Hong, X. et al. in J. Am. Chem. Soc. 2019, 141, 45, 18318-18324, the material is represented as COE-6.

[0005] In view of the progress related to the synthesis of zeolitic materials having an IWR framework structure, methods for obtaining zeolitic materials containing other heteroatoms in their framework structure have been developed. Thus, CN 111847474A relates to the synthesis of Ti-ITQ-24, wherein the framework contains only Si and Ti as tetravalent elements in its structure. The synthesis of Ti-ITQ-24 is also described in US 7344696 B2, wherein B-Ti-ITQ-24 is synthesized in a first step, and subsequently boron is leached from the material via acidic deboronation.

[0006] Despite the results described, there remains a need to provide synthetic procedures for zeolitic materials showing improved physical and chemical properties, particularly in view of their frequent use in catalytic applications. DETAILED DESCRIPTION

[0007] It is therefore an object of the present invention to provide an improved zeolitic material having an IWR-type framework structure and a method for synthesizing the same. Furthermore, it is an object of the present invention to provide an improved zeolitic material for catalytic applications, in particular for heterogeneous catalysis, in particular as an improved zeolitic material as a catalyst in epoxidation reactions. Thus, it was surprisingly found that a zeolitic material having an IWR-type framework structure which contains Si and a further tetravalent element in its framework can be synthesized in particularly high purity and high crystallinity.

[0008] Therefore, the present invention relates to a method for preparing a zeolitic material having an IWR-type framework structure, wherein the method comprises:

[0009] (1) preparing a mixture comprising one or more organic templates as structure directing agents, one or more zeolite materials comprising SiO2 and YO2 in their framework structures, one or more SiO2 sources other than the one or more zeolite materials, and a solvent system, wherein Y is a tetravalent element other than Si;

[0010] (2) heating the mixture obtained in (1) to crystallize the zeolite material having an IWR type framework structure containing SiO2 and YO2 in its framework structure;

[0011] wherein the one or more organic templates comprise an organic dication of formula (I):

[0012] R 3 R 5 R 6 N + -R 1 -QR 2 -N + R 4 R 7 R 8 (I);

[0013] Where R 1 and R 2 independently of one another represent (C1-C3)alkylene, preferably represent C1 alkylene or C2 alkylene, more preferably represent methylene or ethylene, and more preferably represent methylene;

[0014] wherein Q represents C6-arylene, preferably represents 1,4-C6-arylene, and more preferably represents benzene-1,4-diyl;

[0015] Where R 3 and R 4 independently of one another represent (C1-C4)alkyl, preferably represent (C1-C3)alkyl, more preferably represent methyl or ethyl, and more preferably represent methyl; and

[0016] Where R 5 , R 6 , R 7 and R 8 Independently of each other represent (C1-C6)alkyl, preferably represent (C1-C5)alkyl, more preferably represent (C1-C4)alkyl, more preferably represent (C1-C3)alkyl, more preferably represent ethyl, isopropyl or n-propyl, and more preferably represent ethyl or n-propyl.

[0017] Preferably, the one or more zeolite materials in (1) exhibit a framework structure type selected from MFI, MWW, MEL, BEA, CHA, MOR and a mixture of two or more thereof, more preferably, the one or more zeolite materials in (1) exhibit a framework structure type selected from MFI, MWW, BEA and a mixture of two or more thereof, wherein more preferably, the one or more zeolite materials in (1) exhibit an MFI and / or MWW type framework structure.

[0018] Preferably, the tetravalent element Y is selected from Sn, Ti, Zr and a mixture of two or more thereof, more preferably, Y is Sn and / or Ti, wherein more preferably, Y is Ti. According to a particular and preferred embodiment in which Y is Ti, it is preferred that the one or more zeolite materials comprising SiO2 and YO2 in its framework structure in (1) comprise ZMQ-TB and / or TS-1, more preferably TS-1, wherein preferably, the one or more zeolite materials comprising SiO2 and YO2 in its framework structure are ZMQ-TB and / or TS-1, preferably TS-1. In addition and independently thereof, according to a particular and preferred embodiment in which Y is Ti, it is preferred that the zeolite material having an IWR-type framework structure in (2) is Ti-COE-6.

[0019] Preferably, the one or more SiO2 sources other than the one or more zeolite materials are selected from silicates, fumed silica, silica hydrosols, reactive amorphous solid silica, silica gel, silicic acid, colloidal silica, silicates and mixtures of two or more thereof, more preferably, selected from silica hydrosols, silica gel, silicic acid, water glass, sodium metasilicate hydrate, sesquisilicates, disilicates, colloidal silica, tetra(C1-C4)alkylorthosilicates and mixtures of two or more thereof,

[0020] More preferably, it is selected from silica hydrosol, silicic acid, tetra(C2-C3)alkyl orthosilicate and a mixture of two or more thereof,

[0021] More preferably, the one or more SiO sources 2 include tetraethyl orthosilicate, and more preferably, tetraethyl orthosilicate is used as the one or more SiO sources 2.

[0022] Preferably, the alkyl group R 5 and R 6 Combined with each other to form one common alkylene chain, more preferably a (C5-C7)alkylene chain, more preferably a (C5-C6)alkylene chain, more preferably a pentylene or hexylene chain, and more preferably a pentylene chain.

[0023] Preferably, the alkyl group R 7 and R 8 Combined with each other to form one common alkylene chain, more preferably a (C5-C7)alkylene chain, more preferably a (C5-C6)alkylene chain, more preferably a pentylene or hexylene chain, and more preferably a pentylene chain.

[0024] Preferably, the organic dication of formula (I) has formula (II):

[0025]

[0026] Preferably, the one or more organic templates are provided in the form of a salt, more preferably, in the form of one or more salts selected from halides, sulfates, nitrates, phosphates, acetates, hydroxides and mixtures of two or more thereof, more preferably, in the form of one or more salts selected from bromides, chlorides, hydroxides, sulfates and mixtures of two or more thereof, wherein more preferably, the one or more organic templates are provided in the form of hydroxides and / or bromides, and more preferably in the form of hydroxides.

[0027] Preferably, the mixture prepared in (1) further comprises seed crystals, wherein the seed crystals preferably comprise one or more zeolite materials having an IWR type framework structure, more preferably comprise one or more all-silica zeolite materials having an IWR type framework structure, wherein more preferably the seed crystals comprise all-silica ITQ-24, wherein more preferably one or more zeolite materials having an IWR type framework structure are used as seed crystals, more preferably one or more all-silica zeolite materials having an IWR type framework structure, wherein more preferably all-silica ITQ-24 is used as seed crystals.

[0028] In the case where the mixture prepared in (1) further contains seed crystals, it is preferred that the amount of seed crystals contained in the mixture prepared in (1) is in the range of 0.1 wt% to 25 wt%, and more preferably 0.5 wt% to 20 wt%, more preferably 1 wt% to 18 wt%, more preferably 3 wt% to 15 wt%, more preferably 5 wt% to 12 wt%, and more preferably 8 wt% to 9 wt%, based on 100 wt% of one or more SiO2 sources other than the one or more zeolite materials calculated as SiO2.

[0029] Preferably, the mixture prepared in (1) and heated in (2) contains less than 5 wt. %, more preferably less than 3 wt. %, more preferably less than 1 wt. %, more preferably less than 0.5 wt. %, more preferably less than 0.1 wt. %, more preferably less than 0.05 wt. %, more preferably less than 0.01 wt. %, more preferably less than 0.005 wt. %, and more preferably less than 0.001 wt. % Ge, calculated as GeO2 and based on 100 wt. % of one or more SiO2 sources other than the one or more zeolite materials, calculated as SiO2.

[0030] Preferably, the mixture prepared in (1) and heated in (2) contains less than 0.5 wt%, more preferably less than 0.1 wt%, more preferably less than 0.05 wt%, more preferably less than 0.01 wt%, more preferably less than 0.005 wt%, and more preferably less than 0.001 wt% of the trivalent element X, calculated as the element and based on 100 wt% of Si contained in the mixture. Preferably, X is Al and / or B, wherein more preferably, X is Al and B, wherein more preferably, X is Al, B and Ga, and wherein more preferably, X is Al, B, In and Ga.

[0031] Preferably, the mixture prepared in (1) and heated in (2) contains less than 5 wt%, more preferably less than 3 wt%, more preferably less than 1 wt%, more preferably less than 0.5 wt%, more preferably less than 0.1 wt%, more preferably less than 0.05 wt%, more preferably less than 0.01 wt%, more preferably less than 0.005 wt%, and more preferably less than 0.001 wt% of P based on 100 wt% of Si contained in the mixture.

[0032] Preferably, the one or more zeolitic materials comprising SiO2 and YO2 contained in the mixture prepared in (1) and heated in (2) show an Si:Y atomic ratio of Si to the tetravalent element Y in the following range: 5:1 to 500:1, more preferably 10:1 to 250:1, more preferably 20:1 to 150:1, more preferably 25:1 to 100:1, more preferably 30:1 to 70:1, more preferably 32:1 to 50:1, more preferably 34:1 to 42:1, and more preferably 36:1 to 39:1.

[0033] Preferably, the Si:Y atomic ratio of Si to the tetravalent element Y in the mixture prepared in (1) and heated in (2) is in the range of 5 to 1,500, more preferably 10 to 1,000, more preferably 20 to 600, more preferably 30 to 400, more preferably 40 to 250, more preferably 50 to 150, more preferably 60 to 100, and more preferably 70 to 80.

[0034] Preferably, the organic template:Si molar ratio of one or more organic templates to Si in the mixture prepared in (1) and heated in (2) is in the range of 0.01 to 1.5, more preferably 0.05 to 1.2, more preferably 0.1 to 0.9, more preferably 0.15 to 0.7, more preferably 0.2 to 0.5, and more preferably 0.25 to 0.3.

[0035] Preferably, the mixture prepared in (1) further comprises one or more fluoride sources, wherein more preferably, the F:Si atomic ratio in the mixture prepared in (1) and heated in (2) is in the range of 0.01 to 2, preferably 0.05 to 1.5, more preferably 0.1 to 1, more preferably 0.3 to 0.8, and more preferably 0.5 to 0.6. Preferably, the one or more fluoride sources are selected from fluoride salts, HF and mixtures of two or more thereof, more preferably selected from alkali metal fluoride salts, HF and mixtures of two or more thereof, wherein more preferably the one or more fluoride sources comprise HF, wherein more preferably HF is used as the one or more fluoride sources.

[0036] Preferably, the heating in (2) is carried out for a duration ranging from 10 minutes to 10 days, more preferably from 30 minutes to 9 days, more preferably from 1 hour to 8 days, more preferably from 2 hours to 7 days, and more preferably from 3 hours to 6 days, more preferably from 6 hours to 5.5 days, more preferably from 0.5 day to 5 days, more preferably from 1 day to 4.5 days, more preferably from 2 days to 4 days, and more preferably from 2.5 days to 3.5 days.

[0037] Preferably, the heating in (2) is carried out at a temperature in the range of 80 to 220°C, more preferably 110 to 200°C, more preferably 130 to 190°C, more preferably 140 to 180°C, more preferably 150 to 170°C, and more preferably 155 to 165°C.

[0038] Preferably, the heating in (2) is carried out under autogenous pressure, more preferably under solvothermal conditions, more preferably under hydrothermal conditions, wherein the heating in (2) is preferably carried out in a pressure-resistant closed container, preferably in an autoclave.

[0039] Preferably, the method further comprises

[0040] (3) separating the zeolite material obtained in (2),

[0041] and / or

[0042] (4) washing the zeolite material obtained in (2) or (3),

[0043] and / or

[0044] (5) calcining the zeolitic material obtained in (2), (3) or (4), wherein steps (3) and / or (4) and / or (5) may be performed in any order, and

[0045] One or more of the steps are preferably repeated one or more times.

[0046] Preferably, the calcination in (5) is carried out for a duration in the range of 0.5 to 15 hours, more preferably 1 to 10 hours, more preferably 2 to 8 hours, more preferably 3 to 7 hours, more preferably 3.5 to 6.5 hours, more preferably 4 to 6 hours, more preferably 4.5 to 5.5 hours. Additionally and independently, preferably, the calcination in (5) is carried out at a temperature in the range of 300 to 800°C, more preferably 350 to 700°C, more preferably 400 to 650°C, more preferably 450 to 600°C, and more preferably 500 to 550°C.

[0047] Preferably, the solvent system is selected from optionally branched (C1-C4)alcohols, distilled water, and mixtures thereof, more preferably selected from optionally branched (C1-C3)alcohols, distilled water, and mixtures thereof, more preferably selected from methanol, ethanol, distilled water, and mixtures thereof, wherein more preferably, the solvent system comprises distilled water, wherein more preferably, the solvent system consists of distilled water. According to a particular and preferred embodiment wherein the solvent system comprises or consists of distilled water, it is preferred that in the mixture prepared in (1) and heated in (2), the molar ratio of H2O to the one or more sources of SiO2 other than the one or more zeolitic materials, calculated as SiO2, H2O:YO2 is in the range of 0.5 to 15, more preferably 1 to 10, more preferably 1.5 to 5, and more preferably 2 to 3.

[0048] The present invention also relates to a zeolitic material having an IWR-type framework structure obtainable and / or obtained according to the method of any of the particular and preferred embodiments of the present invention.

[0049] Preferably, the zeolite material having an IWR-type framework structure is Ti-COE-6.

[0050] The present invention also relates to the use of a zeolitic material having an IWR-type framework structure according to any of the particular and preferred embodiments of the present invention as a molecular sieve, as an adsorbent, for ion exchange, or as a catalyst and / or as a catalyst support, wherein the zeolitic material is more preferably used as a catalyst in reactions involving C-C bond formation and / or conversion, and preferably as a catalyst in the following reactions: isomerization reactions, ammoxidation reactions, amination reactions, hydrocracking reactions, alkylation reactions, acylation reactions, reactions for converting alkanes into olefins or reactions for converting one or more oxygenates into olefins and / or aromatic compounds, reactions for the synthesis of hydrogen peroxide, aldol condensation reactions, reactions for the isomerization of epoxides. The present invention is preferably used as a catalyst in the following reactions: hydroxylation, Baeyer-Villiger type oxidation, Dakin type reaction or olefin epoxidation, more preferably as an epoxidation of olefins, more preferably an epoxidation of C2-C5 olefins, more preferably an epoxidation of C2-C4 olefins, an epoxidation of C2 or C3 olefins, more preferably an epoxidation of C3 olefins, and more preferably as a catalyst for converting propylene into propylene oxide.

[0051] Preferably, a zeolitic material is used as catalyst for activating hydrogen peroxide.

[0052] The present invention is further illustrated by the following groups of embodiments and combinations of embodiments resulting from the indicated dependencies and back-references. In particular, it should be noted that in each case where the scope of an embodiment is mentioned, for example in the context of a term such as "according to any one of embodiments 1 to 4...", each embodiment within the scope is meant to be explicitly disclosed by a person skilled in the art, i.e., the wording of the term should be understood by a skilled person as being synonymous with "according to any one of embodiments 1, 2, 3 and 4...". In addition, it should be explicitly pointed out that the following group of embodiments is not a group of claims for determining the scope of protection, but rather an appropriate structural part of the description of general aspects and preferred aspects of the present invention.

[0053] 1. A method for preparing a zeolite material having an IWR-type framework structure, wherein the method comprises:

[0054] (1) preparing a mixture comprising one or more organic templates as structure directing agents, one or more zeolite materials comprising SiO2 and YO2 in their framework structures, one or more SiO2 sources other than the one or more zeolite materials, and a solvent system, wherein Y is a tetravalent element other than Si;

[0055] (2) heating the mixture obtained in (1) to crystallize the zeolite material having an IWR type framework structure containing SiO2 and YO2 in its framework structure;

[0056] wherein the one or more organic templates comprise an organic dication of formula (I):

[0057] R 3 R 5 R 6 N + -R 1 -QR 2 -N + R 4 R 7 R 8 (I);

[0058] Where R 1 and R 2 independently of one another represent (C1-C3)alkylene, preferably represent C1 alkylene or C2 alkylene, more preferably represent methylene or ethylene, and more preferably represent methylene;

[0059] wherein Q represents C6-arylene, preferably represents 1,4-C6-arylene, and more preferably represents benzene-1,4-diyl;

[0060] Where R3 and R 4 independently of one another represent (C1-C4)alkyl, preferably represent (C1-C3)alkyl, more preferably represent methyl or ethyl, and more preferably represent methyl; and

[0061] Where R 5 , R 6 , R 7 and R 8 Independently of each other represent (C1-C6)alkyl, preferably represent (C1-C5)alkyl, more preferably represent (C1-C4)alkyl, more preferably represent (C1-C3)alkyl, more preferably represent ethyl, isopropyl or n-propyl, and more preferably represent ethyl or n-propyl.

[0062] 2. A method according to embodiment 1, wherein one or more zeolite materials in (1) exhibit a framework structure type selected from MFI, MWW, MEL, BEA, CHA, MOR and a mixture of two or more thereof, preferably, one or more zeolite materials in (1) exhibit a framework structure type selected from MFI, MWW, BEA and a mixture of two or more thereof, wherein more preferably, one or more zeolite materials in (1) exhibit an MFI and / or MWW type framework structure.

[0063] 3. The method according to embodiment 1 or 2, wherein the tetravalent element Y is selected from Sn, Ti, Zr and a mixture of two or more thereof, preferably, Y is Sn and / or Ti, wherein more preferably, Y is Ti.

[0064] 4. A method according to embodiment 3, wherein Y is Ti, and wherein the one or more zeolite materials containing SiO2 and YO2 in their framework structure contain ZMQ-TB and / or TS-1, preferably TS-1, wherein preferably, the one or more zeolite materials containing SiO2 and YO2 in their framework structure are ZMQ-TB and / or TS-1, preferably TS-1.

[0065] 5. The method according to embodiment 3 or 4, wherein Y is Ti, and wherein the zeolite material having an IWR-type framework structure is Ti-COE-6.

[0066] 6. The method according to any one of embodiments 1 to 5, wherein the one or more SiO2 sources other than the one or more zeolite materials are selected from silicates, fumed silica, silica hydrosols, reactive amorphous solid silica, silica gel, silicic acid, colloidal silica, silicate esters, and mixtures of two or more thereof,

[0067] Preferably selected from silica hydrosol, silica gel, silicic acid, water glass, sodium metasilicate hydrate, sesquisilicate, disilicate, colloidal silicon dioxide, tetra(C1-C4)alkyl orthosilicate and a mixture of two or more thereof,

[0068] More preferably, it is selected from silica hydrosol, silicic acid, tetra(C2-C3)alkyl orthosilicate and a mixture of two or more thereof,

[0069] More preferably, the one or more SiO sources 2 include tetraethyl orthosilicate, and more preferably, tetraethyl orthosilicate is used as the one or more SiO sources 2.

[0070] 7. The method according to any one of embodiments 1 to 6, wherein the alkyl group R 5 and R 6 Combined with each other to form one common alkylene chain, preferably a (C5-C7)alkylene chain, more preferably a (C5-C6)alkylene chain, more preferably a pentylene or hexylene chain, and more preferably a pentylene chain.

[0071] 8. The method according to any one of embodiments 1 to 7, wherein the alkyl group R 7 and R 8 Combined with each other to form one common alkylene chain, preferably a (C5-C7)alkylene chain, more preferably a (C5-C6)alkylene chain, more preferably a pentylene or hexylene chain, and more preferably a pentylene chain.

[0072] 9. The method according to any one of embodiments 1 to 8, wherein the organic dication of formula (I) has formula (II):

[0073]

[0074] 10. The method according to any one of embodiments 1 to 9, wherein the one or more organic templates are provided in the form of a salt, more preferably, in the form of one or more salts selected from halides, sulfates, nitrates, phosphates, acetates, hydroxides and mixtures of two or more thereof, more preferably, in the form of one or more salts selected from bromides, chlorides, hydroxides, sulfates and mixtures of two or more thereof, wherein more preferably, the one or more organic templates are provided in the form of hydroxides and / or bromides, and more preferably in the form of hydroxides.

[0075] 11. The method according to any one of embodiments 1 to 10, wherein the mixture prepared in (1) further comprises seed crystals, wherein the seed crystals preferably comprise one or more zeolite materials having an IWR-type framework structure, preferably comprise one or more all-silica zeolite materials having an IWR-type framework structure, wherein more preferably the seed crystals comprise all-silica ITQ-24, wherein more preferably one or more zeolite materials having an IWR-type framework structure are used as seed crystals, more preferably one or more all-silica zeolite materials having an IWR-type framework structure, wherein more preferably all-silica ITQ-24 is used as seed crystals.

[0076] 12. A method according to embodiment 11, wherein the amount of seed crystals contained in the mixture prepared in (1) is in the range of 0.1 wt. % to 25 wt. %, and preferably 0.5 wt. % to 20 wt. %, more preferably 1 wt. % to 18 wt. %, more preferably 3 wt. % to 15 wt. %, more preferably 5 wt. % to 12 wt. %, and more preferably 8 wt. % to 9 wt. %, based on 100 wt. % of one or more SiO2 sources other than the one or more zeolite materials calculated as SiO2.

[0077] 13. A method according to any one of embodiments 1 to 12, wherein the mixture prepared in (1) and heated in (2) contains less than 5 wt.%, preferably less than 3 wt.%, more preferably less than 1 wt.%, more preferably less than 0.5 wt.%, more preferably less than 0.1 wt.%, more preferably less than 0.05 wt.%, more preferably less than 0.01 wt.%, more preferably less than 0.005 wt.%, and more preferably less than 0.001 wt.% Ge, calculated as GeO2 and based on 100 wt.% of one or more SiO2 sources other than one or more zeolite materials, calculated as SiO2.

[0078] 14. The method according to any one of embodiments 1 to 13, wherein the mixture prepared in (1) and heated in (2) contains less than 0.5 wt.%, preferably less than 0.1 wt.%, more preferably less than 0.05 wt.%, more preferably less than 0.01 wt.%, more preferably less than 0.005 wt.%, and more preferably less than 0.001 wt.% of the trivalent element X, calculated as the element and based on 100 wt.% of Si contained in the mixture.

[0079] 15. The method according to embodiment 14, wherein X is Al and / or B, wherein preferably, X is Al and B, wherein more preferably, X is Al, B and Ga, and wherein more preferably, X is Al, B, In and Ga.

[0080] 16. The method according to any one of embodiments 1 to 15, wherein the mixture prepared in (1) and heated in (2) contains less than 5 wt.%, preferably less than 3 wt.%, more preferably less than 1 wt.%, more preferably less than 0.5 wt.%, more preferably less than 0.1 wt.%, more preferably less than 0.05 wt.%, more preferably less than 0.01 wt.%, more preferably less than 0.005 wt.%, and more preferably less than 0.001 wt.% P based on 100 wt.% of Si contained in the mixture.

[0081] 17. A method according to any one of embodiments 1 to 16, wherein the one or more zeolite materials comprising SiO2 and YO2 contained in the mixture prepared in (1) and heated in (2) exhibits an Si:Y atomic ratio of Si to the tetravalent element Y in the range of 5:1 to 500:1, preferably 10:1 to 250:1, more preferably 20:1 to 150:1, more preferably 25:1 to 100:1, more preferably 30:1 to 70:1, more preferably 32:1 to 50:1, more preferably 34:1 to 42:1, and more preferably 36:1 to 39:1.

[0082] 18. The method according to any one of embodiments 1 to 17, wherein the Si:Y atomic ratio of Si to the tetravalent element Y in the mixture prepared in (1) and heated in (2) is in the range of 5 to 1,500, preferably 10 to 1,000, more preferably 20 to 600, more preferably 30 to 400, more preferably 40 to 250, more preferably 50 to 150, more preferably 60 to 100, and more preferably 70 to 80.

[0083] 19. The method according to any one of embodiments 1 to 18, wherein the organic template:Si molar ratio of the one or more organic templates to Si in the mixture prepared in (1) and heated in (2) is in the range of 0.01 to 1.5, preferably 0.05 to 1.2, more preferably 0.1 to 0.9, more preferably 0.15 to 0.7, more preferably 0.2 to 0.5, and more preferably 0.25 to 0.3.

[0084] 20. A method according to any one of embodiments 1 to 19, wherein the mixture prepared in (1) further comprises one or more fluoride sources, wherein preferably the F:Si atomic ratio in the mixture prepared in (1) and heated in (2) is in the range of 0.01 to 2, preferably 0.05 to 1.5, more preferably 0.1 to 1, more preferably 0.3 to 0.8, and more preferably 0.5 to 0.6.

[0085] 21. The method according to any one of embodiments 1 to 20, wherein the one or more fluoride sources are selected from fluoride salts, HF and a mixture of two or more thereof, preferably selected from alkali metal fluoride salts, HF and a mixture of two or more thereof, wherein more preferably the one or more fluoride sources comprise HF, wherein more preferably HF is used as the one or more fluoride sources.

[0086] 22. The method according to any one of embodiments 1 to 21, wherein the heating in (2) is carried out for a duration ranging from 10 minutes to 10 days, preferably 30 minutes to 9 days, more preferably 1 hour to 8 days, more preferably 2 hours to 7 days, and more preferably 3 hours to 6 days, more preferably 6 hours to 5.5 days, more preferably 0.5 day to 5 days, more preferably 1 day to 4.5 days, more preferably 2 days to 4 days, and more preferably 2.5 days to 3.5 days.

[0087] 23. The method according to any one of embodiments 1 to 22, wherein the heating in (2) is carried out at a temperature in the range of 80 to 220°C, preferably 110 to 200°C, more preferably 130 to 190°C, more preferably 140 to 180°C, more preferably 150 to 170°C, and more preferably 155 to 165°C.

[0088] 24. The method according to any one of embodiments 1 to 23, wherein the heating in (2) is carried out under autogenous pressure, preferably under solvothermal conditions, more preferably under hydrothermal conditions, wherein the heating in (2) is preferably carried out in a pressure-resistant closed container, preferably in an autoclave.

[0089] 25. The method according to any one of embodiments 1 to 24, wherein the method further comprises:

[0090] (3) separating the zeolite material obtained in (2);

[0091] and / or

[0092] (4) washing the zeolite material obtained in (2) or (3);

[0093] and / or

[0094] (5) calcining the zeolite material obtained in (2), (3) or (4),

[0095] wherein steps (3) and / or (4) and / or (5) may be performed in any order, and

[0096] One or more of the steps are preferably repeated one or more times.

[0097] 26. The method according to embodiment 25, wherein the calcination in (5) is carried out for a duration ranging from 0.5 hours to 15 hours, preferably from 1 hour to 10 hours, more preferably from 2 hours to 8 hours, more preferably from 3 hours to 7 hours, more preferably from 3.5 hours to 6.5 hours, more preferably from 4 hours to 6 hours, and more preferably from 4.5 hours to 5.5 hours.

[0098] 27. The method according to embodiment 25 or 26, wherein the calcination in (5) is carried out at a temperature in the range of 300°C to 800°C, preferably 350°C to 700°C, more preferably 400°C to 650°C, more preferably 450°C to 600°C, and more preferably 500°C to 550°C.

[0099] 28. The method according to any one of embodiments 1 to 27, wherein the solvent system is selected from optionally branched (C1-C4) alcohols, distilled water, and mixtures thereof, preferably selected from optionally branched (C1-C3) alcohols, distilled water, and mixtures thereof, more preferably selected from methanol, ethanol, distilled water, and mixtures thereof, wherein more preferably, the solvent system comprises distilled water, wherein more preferably, the solvent system consists of distilled water.

[0100] 29. A method according to embodiment 28, wherein in the mixture prepared in (1) and heated in (2), the molar ratio of H2O to one or more SiO2 sources other than the one or more zeolite materials, calculated as SiO2, is in the following range: 0.5 to 15, preferably 1 to 10, more preferably 1.5 to 5, more preferably 2 to 3.

[0101] 30. A zeolite material having an IWR-type framework structure, which can be obtained by the method described in any one of Embodiments 1 to 29 and / or is obtained by the method described in any one of Embodiments 1 to 29.

[0102] 31. The zeolite material according to embodiment 30, wherein the zeolite material having an IWR-type framework structure is Ti-COE-6.

[0103] 32. Use of a zeolite material according to embodiment 30 or 31 as a molecular sieve, as an adsorbent, for ion exchange, or as a catalyst and / or as a catalyst support, wherein the zeolite material is preferably used as a catalyst in reactions involving C—C bond formation and / or conversion, and preferably as a catalyst in the following reactions: isomerization reactions, ammoxidation reactions, amination reactions, hydrocracking reactions, alkylation reactions, acylation reactions, reactions for converting alkanes into olefins or reactions for converting one or more oxygenates into olefins and / or aromatic compounds, reactions for hydrogen peroxide synthesis, aldol condensation reactions, reactions for epoxide isomerization, transesterification reactions, hydroxylation reactions, Baeyer-

[0104] Villiger-type oxidation reaction, Dakin-type reaction, synthesis of isoprenol, Prins condensation reaction or epoxidation reaction, preferably as a catalyst in the following reactions: hydroxylation reaction, Baeyer-Villiger-type oxidation reaction, Dakin-type reaction or olefin epoxidation reaction, more preferably as an epoxidation reaction of olefins, more preferably the epoxidation reaction of C2-C5 olefins, more preferably the epoxidation reaction of C2-C4 olefins, the epoxidation reaction of C2 or C3 olefins, more preferably the epoxidation reaction of C3 olefins, and more preferably as a catalyst for converting propylene into propylene oxide.

[0105] 33. Use according to embodiment 32, wherein the zeolitic material is used as a catalyst for activating hydrogen peroxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0106] Figure 1 The XRD pattern of TS-1 obtained according to Comparative Example 1 is shown.

[0107] Figure 2 The XRD pattern of the crystalline material obtained according to Comparative Example 1 is shown.

[0108] Figure 3 An SEM image of the crystalline material obtained according to Comparative Example 1 is shown.

[0109] Figure 4 The XRD pattern of Ti-COE-6 obtained according to Example 1 is shown.

[0110] Figure 5 A SEM image of Ti-COE-6 obtained according to Example 1 is shown.

[0111] Experimental Section

[0112] Characterization by X-ray diffraction analysis

[0113] The X-ray diffractometer was used with a Rigaku Ultimate VI (40 kV, 40 mA) using CuKα The X-ray powder diffraction (XRD) pattern was measured by irradiation.

[0114] Characterization by SEM and TEM

[0115] Scanning electron microscopy (SEM) experiments were performed on a Hitachi SU-1510 electron microscope. Transmission electron microscopy (TEM) experiments were performed on a JEOL JEM-2100P at 200 kV.

[0116] K-80 Test

[0117] Experimental Procedure

[0118] At room temperature, 24g of deionized water and 5.2g of 40% by weight hydrogen peroxide solution were placed in a clean 100ml flask with a magnetic stirring bar and a thermometer. At this point, about 0.3ml of the t=0 probe was taken out with a pipette. The flask was gently plugged and then immersed in a pre-balanced thermostat set at 80°C. In order to obtain reproducible results, it is important to always use the same amount of catalyst during the experiment and control the temperature to more than ±1°C. Once the hydrogen peroxide solution reaches thermal equilibrium with the thermostat, 400mg (±1mg) of catalyst (powder or extrudate) was added. The suspension was stirred and then a sample of the supernatant was taken out at regular intervals. A 1mL syringe with a one-way filter Millipore Millex-HV SLHV 013NL (serial number 4875160) or equivalent should be used to extract the probe. First, 0.6ml of the solution was sucked into the syringe through the filter. Then 0.3ml of the solution was backwashed into the flask through the filter. This is necessary to minimize the loss of the catalyst. The remaining 0.3 ml in the syringe was then used for the peroxide determination. The interval between probes was typically between 30 min and 60 min, depending on the catalyst activity.

[0119] The experiment was completed after 7 hours.

[0120] analyze

[0121] The probe is analyzed for H2O2 content by titration using a standard cerium. It is advisable to analyze the probe as soon as possible after collection. To ensure good accuracy, the amount of titration solution used should be at least 5 ml. If necessary, larger amounts of probe must be weighed in.

[0122] Data analysis

[0123] The natural logarithm of the H2O2 concentration is plotted against time. It is important to always use the same units when comparing data (e.g., H2O2 concentration in wt% and time in hours). The plot generally gives a good straight line. The slope is extracted using the least squares method. The slope is the pseudo-first order decay rate (in h) of H2O2 in the presence of the catalyst. -1 Calculated) and called the k80 value.

[0124] Materials used for synthesis

[0125] p-Xylene dibromide (C8H8Br2, 97%, Aladdin Chemical Co., Ltd.), tetraethyl orthosilicate (C8H 20 O4Si, TEOS, 99%, Aladdin Chemical Co., Ltd.), hydrofluoric acid (HF, AR, 40%, Aladdin Chemical Co., Ltd.), 1-methylpyrrolidine (C5H 11 N, 98%, Aladdin Chemical Co., Ltd.), acetonitrile (C2H3N, AR, 99%, Sinopharm Chemical Reagent Co., Ltd.), titanium butoxide (C 16 H 36 O4Ti, 99%, Aladdin Chemical Co., Ltd.

[0126] Reference Example 1: Synthesis of TS-1

[0127] For gel preparation, 500 g of tetraethyl orthosilicate (TEOS) and 15 g of tetraethyl orthotitanate (TEOTi; Merck) were charged into a beaker. Then, 300 g of deionized water and 220 g of an aqueous solution of tetrapropylammonium hydroxide (TPAOH; 40 wt % dissolved in water) were added under stirring (200 rpm). The pH of the resulting mixture was 13.83. The mixture was hydrolyzed at room temperature for 60 minutes, during which the temperature was raised to 60° C. The pH of the mixture was now 12.71. The ethanol was then distilled off until the temperature of the bottom tank reached 95° C. 558 g of distillate were obtained from the distillation.

[0128] The synthesis gel was then cooled to 40° C. with stirring, and 558 g of deionized water were added thereto. The pH of the resulting mixture was 11.95.

[0129] The synthesis gel is then transferred to an autoclave. The synthesis gel is heated to a temperature of 175° C. in an autoclave under stirring and stirred at the temperature for 16 h under autogenous pressure. The pressure is in the range of 8.4 bar to 11.4 bar (absolute pressure). The resulting suspension is then post-processed. For this purpose, the resulting suspension is diluted with deionized water, wherein the weight ratio of the suspension to the deionized water is 1:1. Then, about 152 g of nitric acid (10% by weight dissolved in water) is added, and the pH of the resulting mixture is 7.21. The resulting solid is filtered out and washed three times with deionized water (using 1000 ml of deionized water each time). Subsequently, the solid is dried in an oven at 120° C. in air for 4 h, and then calcined in air at 490° C. for 5 h, wherein the heating rate of calcination is 2° C. / min.

[0130] The Si content of the obtained TS-1 material was 43 wt%, the Ti content was 2 wt%, and the total carbon loss was less than 0.1 wt%. The BET specific surface area of ​​the obtained TS-1 material was 447 m 2 The crystallinity was 92%, and about 0.5% of anatase could be detected by X-ray diffraction.

[0131] Then, 382.0g of deionized water is provided in a beaker. 150.9g of tetrapropylammonium hydroxide (as an aqueous solution containing 40% by weight of tetrapropylammonium hydroxide) is added under stirring. Subsequently, 71.0g of TS-1 material is added. The mixture is homogenized for 30min. The mixture is then transferred to an autoclave. The mixture is hydrothermally treated at 170°C for 6 hours. The resulting solid is separated by centrifugation, and the resulting solid residue is washed with deionized water. The resulting solid is dried at 120°C in air for 4h, and calcined at 490°C in air in an oven for 5h.

[0132] The Si content of the obtained TS-1 product was 44 wt%, the Ti content was 1.9 wt%, and the total carbon loss was less than 0.1 wt%. The BET specific surface area of ​​the obtained TS-1 product was 446 m 2 / g, and the water adsorption amount was 7.25 wt %. The crystallinity was 93%, and about 0.7% of anatase could be detected by X-ray diffraction.

[0133] exist Figure 1 , the XRD pattern of TS-1 material is shown.

[0134] Reference Example 2: Synthesis of p-xylene-bis((N-methyl)N-pyrrolidinium) hydroxide

[0135] In the typical example for the synthesis of organic template, 13.2g p-xylene dibromide is dissolved in 250mL acetonitrile, then 10.6g 1-methylpyrrolidine is added, and stirred 48 hours under reflux.After being cooled to room temperature, the mixture is filtered and washed three times with acetonitrile.Solid is dried overnight under vacuum.Use the hydroxide exchange resin in water that bromide cation is converted into hydroxide form, and use 0.1M HCl as titration that the solution obtained is titrated.

[0136] Comparative Example 1: Synthesis of titanium zeolite having an IWR-type framework structure

[0137] 0.5 g of TS-1 obtained according to Reference Example 1 was added to a solution of p-xylene-bis((N-methyl)N-pyrrolidinium) hydroxide (4.25 g, 0.98 mmol / g) obtained from Reference Example 2 in a 25 mL beaker. After stirring for 2 hours, 0.36 mL of hydrofluoric acid (40% aqueous solution) was added to the above solution, and the beaker was placed in an oven at 80°C to evaporate excess water. Finally, 0.03 g of pure silica IWR seeds (using the same organic template to synthesize the seeds) was added to the above mixture, and the mixture was then ground. The final molar composition of the mixture was 1.0SiO2:0.5OSDA:0.0263TiO2:1HF:2H2O. After grinding, the powder was transferred to a Teflon-lined autoclave and sealed, and crystallized at 160°C for 72 hours under rotating conditions (50 rpm).

[0138] exist Figure 2 In the figure, the XRD pattern of the crystalline material is shown. Figure 3 , a TEM image of the crystalline material is shown.

[0139] from Figure 2 It can be seen from the XRD pattern in that there is still a small amount of TS-1 in the final product.

[0140] Example 1: Synthesis of high purity titanium zeolite (Ti-COE-6) with IWR framework structure

[0141] 0.25 g of TS-1 obtained according to Reference Example 1 was added to a solution of p-xylene-bis((N-methyl)N-pyrrolidinium) hydroxide (3.375 g, 0.75 mmol / g) obtained in Reference Example 2 in a 25 mL beaker, and then 1.274 g of tetraethyl orthosilicate (TEOS) was added to the mixture. After stirring for 12 hours, 0.22 mL of hydrofluoric acid (40% aqueous solution) was added to the above solution, and the beaker was placed in an oven at a temperature of 80° C. to evaporate excess water and ethanol. Finally, 0.03 g of pure silica IWR seeds (using the same organic template to synthesize the seeds) was added to the above mixture, and the mixture was then ground. The final molar composition of the mixture was 1.0SiO2:0.25OSDA:0.0133TiO2:0.5HF:2H2O. After grinding, the powder was transferred to a Teflon-lined autoclave and sealed, and crystallized at 160°C for 72 hours under rotating conditions (50 rpm).

[0142] exist Figure 4 In the figure, the XRD pattern of Ti-COE-6 material is shown. Figure 5 , a TEM image of Ti-COE-6 material is shown.

[0143] from Figure 4 The XRD pattern in FIG. 1 shows that the crystalline material of Comparative Example 1 has a Figure 2 ), the TI-COE-6 material obtained according to Example 1 has a very high purity, wherein no trace of TS-1 starting material is found in the diffraction pattern. Figure 5 As can be seen from the TEM image shown in FIG. 1 , compared with the TEM image of the crystalline material from Comparative Example 1 (see Figure 3 ), the crystals of the Ti-COE-6 material obtained according to Example 1 are significantly larger.

[0144] The K-80 test applied to the Ti-COE-6 material obtained according to Example 1 provided a value of 0.0617 h -1 K-80 value.

[0145] Thus, it has surprisingly been found that by using the process of the invention, it is possible to obtain Ti-COE-6 having very high purity and furthermore showing primary crystallites of large size. Furthermore, from the results of the K-80 test it can be seen that the Ti-COE-6 material is able to activate hydrogen peroxide.

[0146] Cited prior art :

[0147] -EP 1 609 758 B1

[0148] -Cantin, A. et al., J. Am. Chem. Soc. 2006, 128, pp. 4216-4217

[0149] -Shamzhy, M. et al., Catal. Today 2015, 243, 76-84

[0150] -WO 2020 / 244630 A

[0151] -Hong, X. et al., J. Am. Chem. Soc. 2019, 141, 45, 18318-18324

[0152] -CN 111847474 A

[0153] -US 7344696 B2

Claims

1. A method for preparing a zeolite material having an IWR-type framework structure, wherein the method comprises: (1) preparing a mixture comprising one or more organic templates as structure directing agents, one or more zeolite materials comprising SiO2 and YO2 in their framework structures, one or more SiO2 sources other than the one or more zeolite materials, and a solvent system, wherein Y is a tetravalent element other than Si; (2) heating the mixture obtained in (1) to crystallize the zeolite material having an IWR type framework structure containing SiO2 and YO2 in its framework structure; wherein the one or more organic templates comprise an organic dication of formula (I): R 3 R 5 R 6 N + -R 1 -Q-R 2 -N + R 4 R 7 R 8 (I); Where R 1 and R 2 independently of one another represent (C1-C3)alkylene; wherein Q represents a C6-arylene group; Where R 3 and R 4 independently of one another represent (C1-C4)alkyl; and Where R 5 , R 6 , R 7 and R 8 independently of one another represent (C1-C6)alkyl.

2. The method according to claim 1, wherein the one or more zeolite materials in (1) exhibit a framework structure type selected from the group consisting of MFI, MWW, MEL, BEA, CHA, MOR and a mixture of two or more thereof.

3. The method according to claim 1 or 2, wherein the tetravalent element Y is selected from Sn, Ti, Zr and a mixture of two or more thereof.

4. The method of claim 3, wherein Y is Ti, and wherein the one or more zeolite materials comprising SiO2 and YO2 in their framework structure comprise ZMQ-TB and / or TS-1.

5. The method according to any one of claims 1 to 4, wherein the alkyl group R 5 and R 6 bonded to each other to form a common alkylene chain.

6. The method according to any one of claims 1 to 5, wherein the alkyl group R 7 and R 8 bonded to each other to form a common alkylene chain.

7. The method according to any one of claims 1 to 6, wherein the organic dication of formula (I) has formula (II):

8. The method according to any one of claims 1 to 7, wherein the mixture prepared in (1) and heated in (2) contains less than 5 wt. % Ge, calculated as GeO2 and based on 100 wt. % of one or more SiO2 sources other than the one or more zeolite materials, calculated as SiO2.

9. The method according to any one of claims 1 to 8, wherein the mixture prepared in (1) and heated in (2) contains less than 0.5 wt. % of the trivalent element X, calculated as the element and based on 100 wt. % of Si contained in the mixture.

10. The method according to claim 9, wherein X is Al and / or B.

11. The method according to any one of claims 1 to 10, wherein the mixture prepared in (1) further comprises one or more fluoride sources.

12. The method of claim 11, wherein the one or more fluoride sources are selected from the group consisting of fluoride salts, HF, and mixtures of two or more thereof.

13. The method according to any one of claims 1 to 12, wherein the heating in (2) is performed at a temperature in the range of 80°C to 220°C.

14. A zeolite material having an IWR-type framework structure, the zeolite material being obtainable by and / or being obtainable by the method according to any one of claims 1 to 13.

15. Use of the zeolitic material according to claim 14 as molecular sieve, as adsorbent, for ion exchange or as catalyst and / or as catalyst support.